Asymmetric Construction of Axially Chiral 2‐Arylpyrroles by Chirality Transfer of Atropisomeric Alkenes. Issue 38 (12th August 2019) - Wang, Yong‐Bin; Wu, Quan‐Hao; Zhou, Zhi‐Peng; Xiang, Shao‐Hua; Cui, Yuan; Yu, Peiyuan; Tan, Bin
Abstract: Axially chiral 2‐arylpyrrole frameworks are efficiently accessed through a direct chirality transfer strategy by rapid cyclization of enantioenriched atropisomeric alkenes, which are generated by organocatalytic asymmetric N‐alkylation reactions. This approach accommodates a broad scope of substrates with remarkably high chirality transfer efficiency, affording novel atropisomers with a fully substituted pyrrole moiety and high enantiopurities. Given the enantioenriched atropisomeric alkenes, novel heterocyclic 2‐arylazepine atropisomers were realized through a rationally designed ene reaction. Abstract : Axially chiral 2‐arylpyrrole frameworks are efficiently accessed through a direct chirality transfer strategy by rapid cyclization of enantioenriched atropisomeric alkenes, generated by organocatalytic asymmetric N‐alkylation reactions. This approach accommodates a broad scope of substrates with remarkably high chirality transfer efficiency. Given the enantioenriched atropisomeric alkenes, novel heterocyclic 2‐arylazepine atropisomers were realized through a rationally designed ene reaction.